Impact of Covid-19 on Global Economy - R., Venkatesh; S., Abigail; Kumar D., Selva (Journal of Coastal Life Medicine, 2023)
The effects of the CoVD-19 pandemic on the global economy were studied in this study. Statistics from throughout the world, the cost of oil, government responses, and stock market information were analysed for Covid-19. More than 200 countries have been found to be infected with Covid-19, and the economic impact may outlast any negative health effects. To put it another way, it was a disaster for the economies of oil-dependent countries. To put it another way, the shock of Covid-19 isn't going to have as much of an impact on the spread as the severe steps used to stop it. These results suggest that governments should coordinate on the creation of medical procedures to curb the disease's spread, as well as economic policies aimed at the productive sectors of the economy. In order to alleviate the suffering of consumers and businesses, greater aid will be needed.